2019
DOI: 10.1021/acs.joc.9b02029
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective N-Addition/Substitution Reaction of α-Alkylidene Pyrazolinones with Propargyl Sulfonium Salts to Construct Allylthio-Containing Pyrazolones

Abstract: The regioselective N-addition/substitution reaction between α-alkylidene pyrazolinones and propargyl sulfonium salts has been developed to construct functionalized allylthio-containing pyrazolones with moderate to excellent yields. α-Alkylidene pyrazolinones act as N-nucleophilic agents which are distinguished from reported C-nucleophilic reactions. Excellent regioselectivity, readily available starting materials, the broad range of substrates, gram-scale synthesis, and simple operation illustrate the syntheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Recently our group reported the first regioselective NaOAc·3H 2 O-promoted N-addition/substitution reaction between α-alkylidene pyrazolinones and propargyl sulfonium salts ( Scheme 1c ). 14 Accidentally, we found that strong inorganic bases can efficiently promoted the rearrangement of sulfur salts. Based on our processive interests on constructing functionalized pyrazolones and exploring the diverse reactive pathway of propargyl sulfonium salts, 9,15 we herein report the realization of regioselective NaOAc·3H 2 O/KOH-promoted N-addition/[2,3]-sigmatropic rearrangement reaction of α-alkylidene pyrazolinones and propargyl sulfonium salts, delivering bioactive homoallyl sulfur-containing pyrazolones in moderate to excellent yields ( Scheme 1d ).…”
Section: Introductionmentioning
confidence: 91%
“…Recently our group reported the first regioselective NaOAc·3H 2 O-promoted N-addition/substitution reaction between α-alkylidene pyrazolinones and propargyl sulfonium salts ( Scheme 1c ). 14 Accidentally, we found that strong inorganic bases can efficiently promoted the rearrangement of sulfur salts. Based on our processive interests on constructing functionalized pyrazolones and exploring the diverse reactive pathway of propargyl sulfonium salts, 9,15 we herein report the realization of regioselective NaOAc·3H 2 O/KOH-promoted N-addition/[2,3]-sigmatropic rearrangement reaction of α-alkylidene pyrazolinones and propargyl sulfonium salts, delivering bioactive homoallyl sulfur-containing pyrazolones in moderate to excellent yields ( Scheme 1d ).…”
Section: Introductionmentioning
confidence: 91%
“…FT-IR: 692, 756, 1407, 1498, 1610, 1715, 2815, 2962 7, 119.2, 125.4, 126.1, 128.9, 129.0, 130.8, 138.2, 154.8, 170.3. FT-IR: 690, 756, 1118, 1331, 1458, 1496, 1595, 1716, 2952 (Shen et al, 2019) White crystals, MP: 152°C, 1 H NMR (400 MHz, CDCl 3 ): δ 3.81 (s, 2H), 7.48 (brs, 3H), 7.53 (d, 2H, J = 8.0 Hz), 7.75 (d, 2H, J = 4.0 Hz), 7.91 (d, 2H, J = 8.0 Hz). 13 C NMR (100 MHz, CDCl 3 ): δ 39.…”
Section: Chemistrymentioning
confidence: 99%
“…HRMS (ESI) calcd for C 15 H 13 N 2 O (M + H + ), 237.1022; found, 237.1021. (Shen et al, 2019) White crystals, MP: 152°C, 1 H NMR (400 MHz, CDCl 3 ): δ 3.81 (s, 2H), 7.48 (brs, 3H), 7.53 (d, 2H, J = 8.0 Hz), 7.75 (d, 2H, J = 4.0 Hz), 7.91 (d, 2H, J = 8.0 Hz). 13 C NMR (100 MHz, CDCl 3 ): δ 39.…”
Section: Chemistrymentioning
confidence: 99%
“…Different from vinylsulfonium salts, prop-2-ynylsulfonium salts could isomerize to allenic sulfonium salts under basic conditions and be attacked by a nucleophile at the β-carbon atom first. The obtained zwitterionic intermediate B and the resonance structure B′ can undergo a similar process to access α-regioselective intermediate C and γ-regioselective intermediate D .…”
mentioning
confidence: 99%